611. Placental Pathology and Neonatal Outcomes in Pregnancies of Perinatally vs. Nonperinatally HIV-Infected Women. (26th November 2018) - Zeineddine, Nabil; Keating, Maria; Epstein, Shara; Nkwihoreze, Hervette; Aaron, Erika; Alleyne, Gregg; Momplaisir, Florence
Abstract: Background: Perinatally HIV-infected (PHIV) women are reaching childbearing age, but little is known about the impact of long-term exposure to HIV and antiretroviral therapy on pregnancy outcomes of PHIV women, including the impact on neonatal health and placental pathology. Methods: We performed a retrospective cohort analysis over a 10-year period (2007–2017) of PHIV women, matched by age and date of delivery in 1:2 ratio, to behaviorally HIV-infected women (BHIV). The primary maternal outcome variable included virologic suppression (viral load ≤ 400 copies/mL) at delivery. Secondary outcome variables included hospital length of stay (LOS), mode of delivery, infectious (chorioamnionitis, funisitis) and vascular (vasculitis) placental complications based on histopathological analysis of placental specimen (composite variable). The primary neonatal outcome was preterm birth (<37 weeks); secondary neonatal outcomes included APGAR scores and infant HIV status. Primary and secondary maternal and neonatal outcomes were compared between PHIV and BHIV women. Logistic regression models measured the association between primary maternal and neonatal outcomes and perinatal status, adjusting for age and race. Results: A total of 60 deliveries were evaluated during the study period (20 from women with PHIV and 40 from BHIV). Women with PHIV were significantly younger (20 vs. 29, P < 0.05) and less likely to be suppressed at delivery (55% vs. 90%, P < 0.05) compared with women with BHIV. A total of 19 women experienced placental pathologies but no differences were found by perinatal status (31% vs. 36%, P = 0.7, among PHIV and BHIV, respectively). Other than viral suppression, there were no significant differences among maternal and neonatal outcomes of interest by mode of HIV acquisition. In the multivariable regression, women with PHIV were significantly less likely to be suppressed after adjusting for age and race (AOR 0.07, 95% CI 0.01–0.80). There was no significant difference for preterm birth. Conclusion: Women with PHIV were significantly less likely to be suppressed at delivery but did not experience other complications at birth. Neonatal outcomes were similar among women with PHIV and BHIV. Disclosures: All authors: No reported disclosures.